2018
DOI: 10.1186/s12882-018-1088-x
|View full text |Cite
|
Sign up to set email alerts
|

Status of vitamin D and parameters of calcium homeostasis in renal transplant recipients in Nepal: a cross sectional study

Abstract: BackgroundVitamin D, apart from being an important part of the “calcium-vitamin D-parathyroid hormone” endocrine axis, has diverse range of “non-calcemic” biological actions. A high prevalence of vitamin D deficiency has been observed in renal transplant recipients (RTRs) worldwide. This study aimed to determine the prevalence of hypovitaminosis D in Nepalese RTRs and interrelations between serum 25-hydroxyvitamin D [25(OH) D] and other biochemical parameters.MethodsA total of 80 adult RTRs visiting a universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…The majority of patients from nephrology at RMH were treated for chronic kidney disease (CKD). Vitamin D levels are generally low in these patients, as CKD is associated with low levels of vitamin D, especially in patients with end-stage renal disease and kidney transplant recipient 55–59. Our findings are consistent with results from previous studies that demonstrated the association between low vitamin D levels and CKD.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of patients from nephrology at RMH were treated for chronic kidney disease (CKD). Vitamin D levels are generally low in these patients, as CKD is associated with low levels of vitamin D, especially in patients with end-stage renal disease and kidney transplant recipient 55–59. Our findings are consistent with results from previous studies that demonstrated the association between low vitamin D levels and CKD.…”
Section: Discussionsupporting
confidence: 91%
“…In the elderly, a significant negative correlation between serum 25(OH)D and corrected serum calcium was found [ 45 ]. Conversely, there was no significant correlation between serum 25(OH)D and corrected total serum calciumin some reports [ 46 , 47 ]. Besides hypovitaminosis D, causes of hypocalcemia include hypoparathyroidism [ 48 ], intestinal malabsorption, magnesium depletion [ 49 ] and hyperphosphatemia [ 30 ].…”
Section: Discussionmentioning
confidence: 96%
“…В то же время известно, что сывороточный магний не является надежным маркером его содержания в организме и при нормальном его уровне в крови возможна магниевая недостаточность [27]. Не установлено также взаимосвязи между плазменными концентрациями ПТГ и витамина D в отличие от исследования Timalsina S. et al [18]. Более того, витамин D у всех реципиентов и с нормальной и с гиперфункцией ОЩЖ был ниже принятого в общей популяции целевого диапазона [29].…”
Section: Discussionunclassified
“…Факторами риска развития ГПТ в посттрансплантационном периоде явились длительность диализной терапии более 18…”
Section: материалы и методыunclassified
See 1 more Smart Citation